Development of novel bacterial cellulose composites for the textile and shoe industry. Issue 4 (22nd May 2019) - Fernandes, Marta; Gama, Miguel; Dourado, Fernando; Souto, António Pedro
Summary: This research aimed at producing malleable, breathable and water impermeable bacterial cellulose‐based nanocomposites, by impregnating bacterial cellulose (BC) membranes with two commercial hydrophobic polymers used in textile finishing, Persoftal MS (polydimethylsiloxane) and Baygard EFN (perfluorocarbon), by an exhaustion process. These hydrophobic products penetrated the BC membranes and adsorbed tightly onto the surface of the nanofibres, across the entire depth of the material, as demonstrated by Scanning Electron Microscopy and Fourier Transform Infrared spectroscopy studies. The water static contact angles, drop absorption over time and vapour permeability values showed that the composites were impermeable to liquid water but permeable to water vapour. The mechanical properties of the BC‐nanocomposites were improved after incorporation of the hydrophobic products, in some of the formulations tested, overall presenting a satisfactory performance. Thus, through a simple and cost‐effective process, hydrophobized, robust, malleable and breathable nanocomposites based on BC were obtained, featuring promising properties for application in the textile and shoe industries. Abstract : This research aimed at producing malleable, breathable and water impermeable bacterial cellulose‐based nanocomposites, by impregnating bacterial cellulose (BC) membranes with two commercial hydrophobic polymers used in textile finishing by an exhaustion process. The water static contact angles, drop absorption over time and vapor permeability values showed that the composites were impermeable to liquid water but permeable to water vapor. The mechanical properties of the BC‐nanocomposites were improved after incorporation of the hydrophobic products, in some of the formulations tested, overall presenting a satisfactory performance. Thus, through a simple and cost‐effective process, hydrophobized, robust, malleable and breathable nanocomposites based on BC were obtained, featuring promising properties for application in the textile and shoe industries.